2014
DOI: 10.5194/bg-11-5425-2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three vegetation monoterpene emission models to measured gas concentrations with a model of meteorology, air chemistry and chemical transport

Abstract: Abstract. Biogenic volatile organic compounds (BVOCs) are essential in atmospheric chemistry because of their chemical reactions that produce and destroy tropospheric ozone, their effects on aerosol formation and growth, and their potential influence on global warming. As one of the important BVOC groups, monoterpenes have been a focus of scientific attention in atmospheric research. Detailed regional measurements and model estimates are needed to study emission potential and the monoterpene budget on a global… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 81 publications
(92 reference statements)
3
29
0
Order By: Relevance
“…In boreal forests, the growth of the particles is dominated by condensation of organic compounds formed from oxidation of biogenic volatile organic compounds (BVOCs) emitted by the vegetation . Studies have shown that NPF can provide a significant amount of CCN and thereby have a substantial climate impact (e.g., Jokinen et al, 2015;Kerminen et al, 2012;Merikanto et al, 2009;Scott et al, 2014;Spracklen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In boreal forests, the growth of the particles is dominated by condensation of organic compounds formed from oxidation of biogenic volatile organic compounds (BVOCs) emitted by the vegetation . Studies have shown that NPF can provide a significant amount of CCN and thereby have a substantial climate impact (e.g., Jokinen et al, 2015;Kerminen et al, 2012;Merikanto et al, 2009;Scott et al, 2014;Spracklen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In many studies (e.g., Bergström et al, 2012;Farina et al, 2010;Fountoukis et al, 2014;Hodzic et al, 2009;Lane et al, 2008;Murphy et al, 2012) the vapors are assumed to be semi-volatile and in equilibrium with the (liquid, well-mixed) particles, making it possible to model formation of BSOA by simple gas-particle equilibrium partitioning (Pankow, 1994). In other studies (e.g., Scott et al, 2015;Spracklen et al, 2008;Tunved et al, 2010;Westervelt et al, 2013) the vapors are assumed to be nonvolatile and the irreversible particle growth is only limited by the collision rate between the vapor molecules and the particles. Recently, large-scale model studies (Jokinen et al, 2015;Langmann et al, 2014;Li et al, 2015;Riipinen et al, 2011;Yu, 2011) have included both mechanisms to be able to treat semi-volatile and nonvolatile vapors, which have yielded a better agreement between model results and observations.…”
Section: Introductionmentioning
confidence: 99%
“…Longer time series have also consisted of measurements from May to September only (Räisänen et al, 2009;Taipale et al, 2011). This has had a direct effect on the capability of models to predict monoterpene concentrations (Smolander et al, 2014).…”
mentioning
confidence: 99%
“…The most abundant volatile monoterpene, emitted mainly by coniferous trees (i.e. Pinus canariensis), is α-pinene (AndreaniAksoyoglu and Keller, 1995;Rinne et al, 2009;Smolander et al, 2014) and the tracers related to its photochemical oxidation (SOA PIN) are cis-pinonic acid, 3-hydroxyglutaric acid (3-HGA) and 3-methyl-1,2,3-butanetricarboxylic acid (MBTCA) Szmigielski et al, 2007).…”
Section: Tracers Of α-Pinene Oxidation (Soa Pin)mentioning
confidence: 99%